Bulldozers against mosquitoes: Environmental management options for malaria control in North-Central Sri Lanka. [Abstract only]. - Boelee, Eline; Weerasinghe, A.K.; Amerasinghe, Priyanie H.; Piyaratne, M.K.; Perera , D.; Amerasinghe, Felix P. (2005)
In Sri Lanka, malaria is a major public health problem. In some of the remote areas, access to health care and protective measures is hard and larviciding is applied as a supplementary strategy. In the dry zone in North-Central Sri Lanka the main malaria vector responsible for epidemics is Anopheles culicifacies. It breeds in riverbed pools of natural streams such as Yan Oya, which is used as a conveyance canal for downstream irrigation, but not maintained as such. A critical stretch of Yan Oya was selected because of its vector breeding potential and clear association with malaria cases. Mosquito larval populations were monitored bi-weekly from 2000 till 2003; water levels twice a day. Hospital records were complemented with blood slides. In collaboration with the irrigation agency, environmental measures were developed and streambed profiles measured before and after intervention. In the dry season of late 2001 the streambed was cleared of fallen trees, rocks and other barricades, and leveled using heavy machinery and manual labor. Upstream reservoirs and hydraulic structures were repaired for better regulation of the water flow. Costs were shared between the irrigation agency and the project. Larvae of An. culicifacies and An. varuna were found at the stream margins before and after intervention at low flows. After intervention, larval abundance of An. varuna, a secondary malaria vector, increased at two of the sampling points, probably as a result of human activities upstream, such as the construction of temporary dams for irrigation. Natural precipitation and supplementary water releases from the upstream reservoirs increased the water level and reduced breeding levels down to a negligible level within two months. Abundance of An. culicifacies was recorded at very low levels throughout the post-intervention period. Low malaria incidence was reported for the year 2000, and no cases for 2001 and 2002, which might reflect the success of the intervention. However, overall malaria prevalence in the country was also low. Therefore a systematic long-term monitoring program is underway to assess the true impact of the control measures. More than three years after the intervention, the rehabilitated stretch is still visibly different from the untouched part. Additional benefits of the intervention included increased efficiencies of water delivery and reduction of floods in the wet season. Costs of environmental management like this are high for any health intervention, but benefits may stretch over several years and go beyond malaria control. Similar interventions appear feasible at streams elsewhere in South Asia.